Determinan Pengungkapan Islamic Social Reporting (ISR) pada Bank Umum Syariah di Indonesia: Studi Empiris pada Bank Umum Syariah yang Terdaftar di OJK Periode 2019-2023 - Sharifah Aini Nabila; Nelvirita Nelvirita (Jurnal Eksplorasi Akuntansi, 2026)
The purpose of this study is to examine the Islamic social reporting (ISR) disclosure practices that nine Indonesian Islamic commercial banks have put in place between 2019 and 2023. The Sharia Supervisory Board, the company's size, and the ROA were the variables that were taken into account for this specific analysis. Multiple linear regression analysis using SPSS version 2 is used to achieve the investigation's goal. The technique used in this approach is called purposeful sampling. The annual reports that are available on the websites of all Islamic financial institutions were one of the secondary sources of data that were used. The results of this study show that while the size of the Sharia Supervisory Board and the firm have no bearing on ISR disclosure, the degree of profitability has a significant favorable impact.